Harmony of Economic-Based Interfaith Communication - Maesaroh, Maesaroh; Moch Lutfi, Refa Apriatna; Aripudin, Acep (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study examines the role of interfaith communication in creating economic harmony between Hindu and Muslim communities in Taman Lingsar, Lombok. Taman Lingsar is a unique example of collaboration between two different religious groups, where they interact in various religious and economic activities. The aim of this research is to understand how interfaith communication facilitates the creation of mutually beneficial economic synergy, as well as how these two communities cooperate in sectors such as tourism, trade, and local handicrafts. Through a library research approach, this study analyzes relevant literature on interfaith communication and economic synergy. The results of the study show that open and respectful communication between Hindus and Muslims in Taman Lingsar not only strengthens their social relationships but also encourages collaboration in economic activities. This synergy is reflected in the progress of the tourism sector and the improvement of the local community's economic well-being. The study concludes that effective interfaith communication can serve as a model for creating social and economic harmony in areas with religious and cultural diversity.